Analisis Wacana Kritis: Perilaku Bullying dalam Film Kenapa Gue? di Aplikasi Video: Critical Discourse Analysis: Bullying Behavior in the Film Kenapa Gue? on the Video App - Hidayat, Hilda Ramadhita; Rohmadi, Muhammad (Universitas Nusantara PGRI Kediri, 2024)
This study aims to present and reveal the meanings of the impact of bullying as depicted in the film